ANALISIS KINERJA PEGAWAI SEKRETARIAT DPRD KABUPATEN MAMUJU UTARA - Alwi, Alwi (Katalogis, 2016)
This study aims to analyze the performance of the organization secretariat Regency of North Mamuju. This study uses the theory of performance by Agus Dwiyanto, the study is a qualitative research method, to the in formants as many as 10 (ten) informants selected by purposive. Data collection techniques in this study using the method: observation (observation), interviews and documentation. The results of this study indicate that the performance of the organization North Mamuju regency Legislative Secretariat has not run denganbaik. Of 5 (five) dimensions that were examined are four (4) dimensions that have not been going well, namely: (1) productivity shows that the implementation of the task forces employees from the aspect of performance that is seen from an understanding of the duties and office work, the accuracy in the completion of file problems and the number of dispute resolution can not be said to be good (2) Quality of service is seen from the aspect of spontaneity in dealing with issues and complaints serve legislators and the public as well as the courtesy and hospitality in providing services has not been as expected. (3) The responsiveness of services shows that the mechanism has already been made in order to identify the desired needs can thus be concluded that the ministry officials secretariat employees Regency of North Mamuju is responsive to complaints. (4) Responsibility shows that North Mamuju regency legislators are not satisfied with the services provided by employees, in addition to the appointment of personnel lack professional staff in charge of the work that these services are often delayed. (5) Accountability shows that the responsibility of employees at the Parliament Secretariat North Mamuju regency in carrying out its duties and functions are still low.